2021
DOI: 10.21037/jtd-21-150
|View full text |Cite
|
Sign up to set email alerts
|

Does denosumab offer survival benefits? —Our experience with denosumab in metastatic non-small cell lung cancer patients treated with immune-checkpoint inhibitors

Abstract: Background: Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of non-small-cell lung cancer (NSCLC). Denosumab is a humanized monoclonal antibody to RANK ligand used to prevent skeletal-related events of bone metastases in solid tumors. We are reporting the clinical outcomes in our NSCLC patients who received RANKL inhibitor in combination with ICIs. Methods: This observational study used retrospective data from a tertiary cancer center from 2015-2020.Stage IV non-small cell lung cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Theoretically, combining ICIs and RANKL inhibitors may convert the immunosuppressive bone microenvironment to a “hot” one, thus enhancing clinical responses in patients with advanced-stage cancers. The synergistic effect of BMA s+ ICIs has been reported by preclinical studies in other solid tumors (PC, NSCLC, and melanoma) with BoM [ 11 , 12 , 48 ], which demonstrated survival benefits and delay of primary tumor progression. In our study, the efficacy of BMAs with immunotargeted therapy and two types of BMAs in patients with HCC and BoM have been comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Theoretically, combining ICIs and RANKL inhibitors may convert the immunosuppressive bone microenvironment to a “hot” one, thus enhancing clinical responses in patients with advanced-stage cancers. The synergistic effect of BMA s+ ICIs has been reported by preclinical studies in other solid tumors (PC, NSCLC, and melanoma) with BoM [ 11 , 12 , 48 ], which demonstrated survival benefits and delay of primary tumor progression. In our study, the efficacy of BMAs with immunotargeted therapy and two types of BMAs in patients with HCC and BoM have been comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence that regardless of the BoM burden of NSCLC patients, the longer time ICIs and denosumab were used concurrently, the more benefit could be achieved [ 12 , 48 , 49 ]. In clinical practice, patients with BoM may not receive sequential BMAs, especially patients with advanced stages and poor physical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 11 (15.9%) of the patients received prior chemotherapy and 47 (68.1%) of the patients received radiation therapy. Median number of metastatic sites was 4 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. All patients have skeletal metastases and majority of the patients had <3 skeletal metastases (62.3% vs. 37.7%).…”
Section: Resultsmentioning
confidence: 99%
“…According to a posthoc analysis of phase III clinical trial in metastatic lung cancer patients, median overall survival was 8.9 months for patients receiving denosumab compared with 7.7 months for patients receiving zoledronic acid (10). Udagawa et al reported that in chemotherapy naïve non-squamous nonsmall cell lung cancer patients with 80% having bone metastasis and unknown brain metastasis status, the median OS in the denosumab group, zoledronic acid group and no treatment group were 21.4 months, 12.7 months and 10.5 months, respectively (15). Liede and others reported that in NSCLC patients with 76% having Stage IV disease at diagnosis but unknown brain metastasis status, the ORR was 33.1% in patients treated concurrently with denosumab and anti-PD1 mAb (16).…”
Section: Denosumab Is Clinically Indicated In Nsclc Patientsmentioning
confidence: 99%
“…A small number of clinical studies have reported that denosumab is beneficial for the improvement of OS in NSCLC patients with bone metastasis [ 3 , 21 , 26 , 27 ]. The potential factors contributing to the survival benefit of denosumab remain unclear.…”
Section: Discussionmentioning
confidence: 99%